A dog's life : the autobiography of a stray - Martin, Ann M., 1955- (New York : Scholastic, 2007)
A stray puppy named Squirrel relates her life story, beginning with her nurturing mother; providing details of her experiences with both nice and mean humans, busy highways, and the seasons; and ending with her meeting two friends.
"Apple Signature."
4.9
3-6
3-6
School Library Journal
Book Links (A.L.A.)
Keywords: Dogs -- Juvenile fiction; Dogs -- Fiction; Orphaned animals -- Fiction; Dogs -- Fiction; Animals -- Fiction